2018
DOI: 10.1016/j.rboe.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation and pain symptomatology of the knee in severely obese individuals – controlled transversal study

Abstract: ObjectiveTo evaluate the prevalence of pain and radiographic degenerative arthritis in a group of severe obese patients (body mass index [BMI] > 35).Methods41 patients with an indication of bariatric surgery were studied. The group of severely obese patients was subdivided into two subgroups: those with BMI < 50 and those with BMI > 50 (n = 14). They were compared to control group (n = 39). The following parameters were analyzed and correlated: radiographic arthritis by Kellgren-Lawrence's classification, tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(63 reference statements)
0
2
0
2
Order By: Relevance
“…2 Population studies have shown that obesity is an independent risk factor for knee pain and arthrosis. [3][4][5] In obese patients, feet pain incidence has been less studied in the literature than obesity-related knee pain. [3][4][5] Obesity results in feet pain and biomechanical changes secondary to flat foot deformity, plantar fat alterations, decreased muscle strength and gait pattern abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Population studies have shown that obesity is an independent risk factor for knee pain and arthrosis. [3][4][5] In obese patients, feet pain incidence has been less studied in the literature than obesity-related knee pain. [3][4][5] Obesity results in feet pain and biomechanical changes secondary to flat foot deformity, plantar fat alterations, decreased muscle strength and gait pattern abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In obese patients, feet pain incidence has been less studied in the literature than obesity-related knee pain. [3][4][5] Obesity results in feet pain and biomechanical changes secondary to flat foot deformity, plantar fat alterations, decreased muscle strength and gait pattern abnormalities. 6 This process leads to loss of balance and risk of falling, interfering with the mobility of these individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations